Current status and molecular epidemiology of rabies virus from different hosts and regions in Malawi - Henson Kainga; Elisha Chatanga; Marvin Collen Phonera; John Pilate Kothowa; Precious Dzimbiri; Gladson Kamwendo; Malala Mulavu; Cynthia Sipho Khumalo; Katendi Changula; Herman Chambaro; Hayato Harima; Masahiro Kajihara; et al. (Archives of Virology, 2023)
Although rabies is endemic in Malawi, there have been no studies in which rabies virus was systematically investigated and characterized in multiple animal hosts in that country. In order to provide molecular epidemiological data on rabies virus in Malawi, 683 suspected rabies case reports from 2008 to 2021 were examined, and 46 (dog = 40, cow = 5, and cat = 1) viable rabies-positive brain samples archived at the Central Veterinary Laboratory (CVL), Lilongwe, Malawi, were analyzed genetically. The results showed an increase in the submission of brain samples from 2008 to 2010, with the highest number of submissions observed in 2020. Of the 683 case reports analyzed for the period under review, 38.1% (260/683) (CI: 34.44 – 41.84) were confirmed by direct fluorescent antibody test. Among the confirmed cases, 65.4% (170/260) (CI: 59.23 – 71.09) were canine rabies. Further, phylogenetic analysis revealed that sequences from different animal hosts clustered together within the Africa 1b lineage, suggesting that the strains circulating in livestock are similar to those in domestic dogs. This finding supports the hypothesis that canine rabies is spilling over to livestock and emphasizes the need for further studies to provide data for effective control of rabies in Malawi.

Prevalence and genetic diversity of Shibuyunji virus, a novel tick-borne phlebovirus identified in Zambia - Edgar Simulundu; Saidon Mbambara; Herman M. Chambaro; Karen Sichibalo; Masahiro Kajihara; King S. Nalubamba; Hirofumi Sawa; Ayato Takada; Katendi Changula; Simbarashe Chitanga (Archives of Virology, 2021)

Seroprevalence of Rift Valley fever in cattle of smallholder farmers in Kwilu Province in the Democratic Republic of Congo - Abdel-Amir Dib Halawi; Ngonda Saasa; Boniface Lombe Pongombo; Masahiro Kajihara; Herman Moses Chambaro; Mutambel Hity; Hirofumi Sawa; Ayato Takada; Aaron S Mweene; Luamba Lua Nsembo; Edgar Simulundu (Tropical Animal Health and Production, 2019)

Molecular detection and characterization of genotype 1 bovine leukemia virus from beef cattle in the traditional sector in Zambia - Mundia M. Phiri; Evans Kaimoyo; Katendi Changula; Isaac Silwamba; Herman M. Chambaro; Penjaninge Kapila; Masahiro Kajihara; Martin Simuunza; John Bwalya Muma; Girja S. Pandey; Ayato Takada; Aaron S. Mweene; et al. (Archives of Virology, 2019)

First genetic detection and characterization of canine parvovirus from diarrheic dogs in Zambia - James Kapiya; King S. Nalubamba; Evans Kaimoyo; Katendi Changula; Nozyechi Chidumayo; Ngonda Saasa; Martin C. Simuunza; Ayato Takada; Aaron S. Mweene; Simbarashe Chitanga; Edgar Simulundu (Archives of Virology, 2019)

Genetic characterization of orf virus associated with an outbreak of severe orf in goats at a farm in Lusaka, Zambia (2015) - Edgar Simulundu; Nandi Mtine; Thoko F. Kapalamula; Masahiro Kajihara; Yongjin Qiu; James Ngoma; Victor Zulu; Geoffrey Kwenda; Chrispin Chisanga; Isaac K. Phiri; Ayato Takada; Aaron S. Mweene (Archives of Virology, 2017)

Clinical and subclinical bovine leukemia virus infection in a dairy cattle herd in Zambia - Girja S. Pandey; Edgar Simulundu; Danstan Mwiinga; Kenny L. Samui; Aaron S. Mweene; Masahiro Kajihara; Alfred Mangani; Racheal Mwenda; Joseph Ndebe; Satoru Konnai; Ayato Takada (Archives of Virology, 2017)

Molecular characterization of infectious bursal disease viruses detected in vaccinated commercial broiler flocks in Lusaka, Zambia - Kunda Ndashe; Edgar Simulundu; Bernard M Hang’ombe; Ladslav Moonga; Hirohito Ogawa; Ayato Takada; Aaron S Mweene (Archives of Virology, 2016)

Pathological and molecular diagnosis of the 2013 African swine fever outbreak in Lusaka, Zambia - John Yabe; Pharaoh Hamambulu; Edgar Simulundu; Hirohito Ogawa; Masahiro Kajihara; Akina Mori-Kajihara; Katendi Changula-Chitanga; Max Mwase; Mutinta Mweemba-Muwowo; Herman Moses Chambaro; Liywalii Mataa; Bernard Hang’ombe; et al. (Tropical Animal Health and Production, 2015)

The zoonotic potential of avian influenza viruses isolated from wild waterfowl in Zambia - Edgar Simulundu; Naganori Nao; John Yabe; Nilton A. Muto; Thami Sithebe; Hirofumi Sawa; Rashid Manzoor; Masahiro Kajihara; Mieko Muramatsu; Akihiro Ishii; Hirohito Ogawa; Aaron S. Mweene; et al. (Archives of Virology, 2014)

Characterization of H3N6 avian influenza virus isolated from a wild white pelican in Zambia - Edgar Simulundu; Aaron S. Mweene; Daisuke Tomabechi; Bernard M. Hang’ombe; Akihiro Ishii; Yuka Suzuki; Ichiro Nakamura; Hirofumi Sawa; Chihiro Sugimoto; Kimihito Ito; Hiroshi Kida; Lewis Saiwana; et al. (Archives of Virology, 2009)